(untitled) (Journal of the College of Basic Education, 2023)
By (bringing the absent) I mean some of what the rhetoricists have studied in the chapter on paying attention. Arabic dictionaries indicate that (turnip) is a transitive verb by itself, with the meaning of: twist, 1, and from this sensual indication The immanent or metaphor came, so it is said: He turned him away from showing him, that is: turned him away from him, and the friend indicated 2 While (turnip) and (felt) mean the same thing, while Ibn Faris indicated that “the blame and the fulfillment And the word “Taa’” is a single word denoting: to twist, to divert something from its straight direction.” 3 From this linguistic meaning came the meaning